Pengaruh Pendapatan , Jumlah Nasabah Dan Tingkat Suku Bunga Terhadap Penyaluran Kredit Pt Pegadaian Cabang Kabupaten Jember Periode 2013 -2017 - Ratih Rachmawati (STIE Mandala Jember, 2019)
The research objective was to analyze the large number, number of customers, and interest rates on the loan distribution of PT Pegadaian Branch of Jember Regency.The type of data used in this study is secondary data consisting of time series data on income, number of customers obtained through the pawnshop office which is the object of research and interest rates for the period 2013-2017 obtained from BI which is the object of the research. The data is processed using computer software